Limitations of access to internet services in Africa: Communication 742/20,African Freedom of Expression Exchange & 15 Others (represented by FOIAttorneys) v Algeria & 27 Others - (:unkn) unknown (My University, 2024)
The intentional limitation of telecommunications services and internet access on various grounds infringes a broad range of fundamental rights, including freedoms of expression and information, which are necessary in a free and democratic society in the digital age. In a fundamental right approach, states, when resorting to restrictive laws, have the positive obligation to specify, rigorously, their legal necessity, using legistics and ethics of proportion, even if it is laws pursuing legitimate goal to protect public order or national security. Then how can we analyse the decision by the African Commission on Human and Peoples’ Rights to declare inadmissible the Communication by 16 non-governmental organizations, against 28 African States that had interrupted or limited digital access, probably without meeting the requirements of articles 9, 10 and 11 of the African Charter? This contribution discusses the merits of the issue of digital rights, which the African Commission had not been able to examine, due to a lack of specific and substantive allegations and evidence. More specifically, what are the compelling circumstantial indicators of infringement of the freedoms of expression and information on the internet, when the alleged risks of impeding democratic electoral processes are weighed against the imperative need to safeguard national security or public order? It is regrettable that the African Commission was not able to deal with such an important issue simply because it hastily assessed the criteria for admissibility of the petition, thus depriving the complainants of the legal opportunity to clarify the substance of their complaint. Considering, moreover, that the African Commission is a human rights promotion and protection body, the exclusion of ‘entities’ not party to the African Charter, which is entirely justified, does not deprive it of the legal clarifications required when there is reason to believe that they may be responsible f
Keywords: African Research